Gram Positive Bacteria causing Lower Respiratory Tract Infections and their Resistance Patterns in Kathmandu University Hospital - Sherchan, Jatan Bahadur; Humagain, S (Nepal Medical College Journal, 2020)
Respiratory tract infection due to Gram positive bacteria is a common cause of morbidity and mortality worldwide. This study of one year duration was carried out to determine the antibiotic resistance pattern of Gram-positive bacteria from patients with lower respiratory tract infection visiting Kathmandu University Hospital. A total of 1,556 respiratory samples including sputum and endotracheal aspirates were processed following standard guidelines. Antibiotic resistance pattern was determined following Clinical Laboratory Standard Institute guidelines. Gram positive bacteria from total sample were 6.6%. Out of them 86.4% were Streptococcus pneumoniae and 13.6% were Staphylococcus aureus. Majority of S. pneumoniae, 53.9% were resistant to azithromycin, followed by cotrimoxazole 40.4%, ciprofloxacin 13.5% and Ceftriaxone 1.1% but all isolates were sensitive to penicillin. A total of 92.9% S. aureus were methicillin and Ciprofloxacin resistant, 64.3% were resistant to cotrimoxazole and 28.6% resistant to amikacin but all strains were sensitive to linezolid. Majority of multidrug resistant Staphylococcus were detected among patients of age more than 60 years. A total of 77.8% patients had lower respiratory tract infection with acute exacerbation of chronic obstructive pulmonary disease. Majority of diabetic patients had multidrug resistant organism. 70.69% patients of age above 60 had multidrug resistant isolates. Multidrug-resistant Gram positive bacteria were observed in respiratory samples. For effective management of lower respiratory tract infections detailed microbiological diagnosis and susceptibility testing is required.